PERANAN SIFAT-SIFAT KEWIRAUSAHAAN DALAM MENINGKATKAN KINERJA PEMASARAN RUMPUT LAUT (STUDI PADA USAHA RUMPUT LAUT DI PANTAI GEGERNUSA DUA BADUNG) - Kadek, Sanjaya; Enny, Sustyawati (Jurnal Ilmiah Manajemen & Bisnis, 2017)
ABSTRACT The analysis finds that the properties comprising entrepreneurial confidence, and results-oriented tasks, risktakers, leadership, originality and oriented to the future a significant effectin improving marketing performance sea weed farmers, either simultan eously or partially. But one variable that is task-oriented and results have no significant effecton the performance of marketing sea weed farmers of Nusa Dua Badung. Future-oriented variables have the most dominant influence in improving marketing performance sea weed farmers of Nusa Dua Badung. It canbe seen from kefesien standardized beta regression, in which future-oriented variables have the greatest value is 0.449.